The expression of Millennial female journalists’ idealism: experiences of female journalists in Surabaya, Indonesia - Nurdin, Ali; Sulaeman, Sulaeman; Ridwan, M. (Brazilian journalism research, 2022)
ABSTRACT – The existence of women can be actualized through the expression of idealism in the journalist profession. This study aims to describe the expression of idealism and the construction of the identity of millennial female journalists. The study was qualitatively conducted by interviewing ten women journalists using the snowball sampling technique and through analysis based on identity theory. The results indicated that the expression of millennial female journalists’ idealism was enacted via subtle news language, perspectives, or angles prioritizing women’s feelings, the capability to master media technology, and overall professionalism. Outwardly, millennial women journalists were shown to construct their identities by dressing in typical business dress, acting with confidence, and playing the role of a journalist. This media management system was revealed to shape the journalists’ self-constructions of their professional identities as the expression of idealism. RESUMO – A existência de mulheres pode ser atualizada através da expressão do idealismo na profissão de jornalista. Este estudo tem como objetivo descrever a expressão do idealismo e a construção da identidade de mulheres jornalistas millennials. O estudo possui caráter qualitativo e foi conduzido por meio de entrevistas com dez mulheres jornalistas, a partir da técnica de amostragem em bola de neve. As análises foram baseadas na teoria da identidade. Os resultados indicaram que a expressão do idealismo das jornalistas millennials foi representada pela delicadeza da linguagem noticiosa, perspectivas ou ângulos que priorizam os sentimentos das mulheres, a capacidade de dominar a tecnologia midiática e profissionalismo em geral. Externamente, as jornalistas millennials constroem suas identidades vestindo roupas tipicamente relacionadas ao universo dos negócios, agindo com confiança e desempenhando o papel de jornalistas. Esse sistema de gerenciamento de mídia revelou-se para moldar as autoconstruções dos jornalistas de suas identidades profissionais como expressão do idealismo. RESUMEN – La existencia de la mujer puede actualizarse a través de la expresión del idealismo en la profesión periodística. Este estudio tiene como objetivo describir la expresión del idealismo y la construcción de la identidad de las periodistas millennial. El estudio se realizó de forma cualitativa entrevistando a diez mujeres periodistas utilizando la técnica de muestreo de bola de nieve y mediante análisis basados en la teoría de la identidad. Los resultados indicaron que la expresión del idealismo de las periodistas millennial se promulgó a través de un lenguaje sutil de las noticias, perspectivas o ángulos que priorizan los sentimientos de las mujeres, la capacidad de dominar la tecnología de los medios y el profesionalismo general. Exteriormente, se demostró que las mujeres periodistas millennial construyen sus identidades vistiéndose con el traje típico de negocios, actuando con confianza y desempeñando el papel de una periodista. Este sistema de gestión de medios se reveló para dar forma a las autoconstrucciones de los periodistas de sus identidades profesionales como la expresión del idealismo.